PASCAOPERASI ADENOMA HIPOFISIS: HUBUNGAN ANTARA DURASI AWITAN DENGAN LUARAN KLINIS VISUS DAN LAPANG PANDANG - Renindra Ananda Aman; Reki Setiawan; Retno Asti Werdhani; Samsul Ashari; David Tandian; Syaiful Ichwan; Affan Priyambodo; Setyo Widi Nugroho (PERDOSNI, 2020)
Introduction: Pituitary adenomas can cause decrease of visual acuity (VA), narrowing visual field (VF). Several studies have showed that the duration of complaints were related significantly with clinical outcomes. As a national referral center hospital, all pituitary adenoma patients who came to our institution were referred from ophthalmologists, neurologists, and neurosurgeons from other institutions. Aim: In this study, we investigated the relationship between duration, which is calculated from the time of symptoms first appeared to the time of surgery, and outcome (VA and VF) in pituitary adenoma patients who underwent transsphenoidal surgery. Methods: A retrospective design was used on pituitary adenoma patients that underwent transsphenoidal surgery between 2015-2017 in Cipto Mangunkusumo Hospital. The duration between symptoms’ onset and surgery was calculated in months. VA and VF examinations were performed 1 day before surgery and within 1 to 2 months postoperatively. Results: There were 71 patients (36 male, 35 female) with decreased VA and narrowed VF, with a median age of 42 years (20-77 years). The median length of duration of onset for both symptoms was 12 months (1-108 months). 40.5% patients had improved VA postoperatively, with median duration of onset of 11 months. Improvement in VF was experienced in 67.6% patients, with median duration of onset of 12 months. Discussion: There was a statistically significant relationship between the duration of onset and the VF outcomes. Improvements in the VF were found in patients who underwent surgery up to 12 months after the time of onset. Keywords: Pituitary adenoma, transsphenoidal surgery, visual acuity, visual field